Regional grey matter volume reduction in adolescents engaging in non-suicidal self-injury - Ando, Ayaka; Reichl, Corinna; Scheu, Friederike; Bykova, Anastasia; Parzer, Peter; Resch, Franz; Brunner, Romuald; Kaess, Michael (Psychiatry research, 2018)
There is a high prevalence of non-suicidal self-injury (NSSI) amongst adolescents worldwide and therefore an urgency to investigate the underlying mechanisms that may facilitate such behaviours. This study aimed to investigate neurobiological alterations, specifically in regional brain volumes of the frontolimbic system, in adolescents engaging in NSSI in comparison to healthy controls. Regional grey matter volumes were compared between 29 adolescent female patients who presented with incidents of NSSI on ≥5 days within the last 12 months (DSM-5 criteria for NSSI) and 21 healthy age, gender and education matched controls who had never received any psychiatric diagnosis/treatment, or engaged in NSSI. Significant group effects in regional brain volumes were observed in insula, and a suggested change in the anterior cingulate cortex (ACC), while controlling for total segmented volume. Additionally, ACC volume showed a significant association with past suicide attempts, where estimated marginal means showed even smaller ACC volume in adolescents engaging in NSSI with a history of suicide attempt in comparison to those with no history of suicide attempt, including healthy controls. This study provides the first evidence of volumetric changes in adolescents engaging in NSSI and a potential neurobiological link between NSSI and suicide attempt.
Gesehen am 14.05.2020